2010
DOI: 10.1099/ijs.0.013235-0
|View full text |Cite
|
Sign up to set email alerts
|

Agrococcus terreus sp. nov. and Micrococcus terreus sp. nov., isolated from forest soil

Abstract: Two bacterial strains, DNG5T and V3M1T, isolated from forest soil of the Changbai mountains in China, were characterized using a polyphasic approach. Analysis of their 16S rRNA gene sequences indicated that strains DNG5T and V3M1T were phylogenetically related to members of the genus Agrococcus (96.0–98.4 % similarity) and Micrococcus (96.7–98.0 % similarity), respectively, within the order Actinomycetales. Strains DNG5T and V3M1T were Gram-stain-positive and strictly aerobic and formed yellow colonies on LB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 30 publications
(32 reference statements)
1
26
1
Order By: Relevance
“…Therefore, we classified this isolate as A. jejuensis. Members of the genus Agrococcus have been isolated from various environments including soil, cheese surfaces, potato plants and dried seaweed as well as from the air (Zhang, Liu, & Liu, 2010). In this study, an Agrococcus species was isolated for the first time from an insect.…”
Section: Numbermentioning
confidence: 97%
“…Therefore, we classified this isolate as A. jejuensis. Members of the genus Agrococcus have been isolated from various environments including soil, cheese surfaces, potato plants and dried seaweed as well as from the air (Zhang, Liu, & Liu, 2010). In this study, an Agrococcus species was isolated for the first time from an insect.…”
Section: Numbermentioning
confidence: 97%
“…strain HBL-15 revealed that the bacterium did not show any response to increasing salt concentration, and the cellular fatty acid composition was almost similar at all three different concentrations of salt (Table 4). It indicated that, due to structural differences in the cellular envelope of Gram-positive and Gram-negative bacteria (Zhang et al 2010); Micrococcus and Halomonas showed different responses for salt stress. As discussed earlier, iso and anteiso branched-chain fatty acids are characteristic of the Grampositive cell wall, but this kind of fatty acid is lacking in the cell wall of Gram-negative bacteria.…”
Section: Iso Antementioning
confidence: 97%
“…By increasing the incubation time as suggested by [6], we should be able to isolate some members of groups that to date have not been grown in pure culture. According to [14] and [13] the use of serial dilution, liquid culture techniques has proved to be effective for isolating numerically significant members of the community in cultivated and non-cultivated soil samples. However, when this techniques was used to cultivate bacteria from the Nutrient agar, Plate count agar and Soil extract agar, the mean viable count obtained were 45.5%, 36.5% and 18.0% for sample A (cultivated sandy loamy soil) and 51.9%.…”
Section: Discussionmentioning
confidence: 99%